1981
DOI: 10.1056/nejm198110083051501
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Respiratory Syncytial Virus-Specific IgE and the Release of Histamine in Nasopharyngeal Secretions after Infection

Abstract: We studied the development of respiratory syncytial virus (RSV)-specific IgE and the release of histamine in nasopharyngeal secretions from 79 infants with various forms of respiratory illness due to RSV. RSV-IgE was measured by an enzyme-linked immunosorbent assay; specificity was confirmed by appropriate blocking experiments. Histamine content in the secretions was determined by fluorimetric methods. RSV-IgE was detectable in only one of 19 patients with RSV infection without wheezing, but was detectable in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
235
1
7

Year Published

1984
1984
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 509 publications
(251 citation statements)
references
References 19 publications
8
235
1
7
Order By: Relevance
“…The evidence for this can be obtained from cultures, antigen detection, or serologic responses compared with random controls (11)(12)(13). Similar results have been obtained in population-based studies (14).…”
Section: Bronchiolitis and Respiratory Syncitial Virus In The First Tsupporting
confidence: 53%
See 1 more Smart Citation
“…The evidence for this can be obtained from cultures, antigen detection, or serologic responses compared with random controls (11)(12)(13). Similar results have been obtained in population-based studies (14).…”
Section: Bronchiolitis and Respiratory Syncitial Virus In The First Tsupporting
confidence: 53%
“…The relevance of the immune response to RSV has been debated for many years. Welliver and his colleagues reported the presence of nasal IgE antibodies specific for RSV (11 (5,12,13,27). By the time children have reached middle school (10-13 years of age), asthma is very strongly associated with positive skin tests to common inhalant allergens.…”
Section: Bronchiolitis and Respiratory Syncitial Virus In The First Tmentioning
confidence: 99%
“…While herpesvirus infections early in life may help prevent AD, infections with herpes simplex and Coxsackie virus in patients with established AD can lead to eczema herpeticum and Coxsakium, respectively [136,137]. Moreover, some studies found that infections with respiratory syncytial virus may actually increase the risk of disease [73,[75][76][77][78]. Finally, it is well established that patients with AD have increased colonization of both lesional and nonlesional skin with Staphylococcal aureus and decreased microbial diversity [79][80][81][82].…”
Section: Hygiene Hypothesismentioning
confidence: 99%
“…Also, the level of HRSV-specific IgE response after primary infection is useful in predicting future episodes of wheezing (91). Recently, a defect in suppressor cell numbers and function was reported in infants with HRSV-bronchiolitis, which may explain the overproduction of IgE and exaggerated lymphocyte proliferation response (discussed later) in these patients (107). Possibly, the severe form of HRSV infection occurs only in those individuals with a hereditary tendency to overproduce IgE.…”
Section: Prior Sensitising Infection (Type I Hypersensitivity)mentioning
confidence: 99%